Czytanie i edukacja - Nasiłowska, Anna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The author points out the need to develop reading abilities at the stage of school education, arguing that literature not only perpetuates the memory of the past and preserving cultural identity, but also — and perhaps primarily — teaches empathy and shapes cognitive and language skills necessary for those who wish to influence others, thus in fact — for everyone. Reading literature is therefore practical, and should be treated as an integrating subject at schools, rather than a specific type of study. In learning to read, according to the author, we should see initiation conducive to spiritual development for the whole future life.